Are You Ethical? Please Tick Yes □ Or No □ On Researching Ethics in Business Organizations - Crane, Andrew (Journal of business ethics, 1999)
This paper seeks to explore the empirical agenda of business ethics research from a methodological perspective. It is argued that the quality of empirical research in the field remains relatively poor and unconvincing. Drawing on the distinctions between the two main philosophical positions from which methodologies in the social sciences are derived – positivism and interpretism – it is argued that it is business ethics' tradition of positivist, and highly quantitative approaches which may be at the root of these epistemological problems. Six distinct aspects of business ethics research are identified and assessed according to their methodological impact. Accordingly, it is argued that more interpretive approaches may offer substantial liberating potential in the development of a stronger and more theory-rich empirical base. The author concludes by arguing for greater plurality and diversity in empirical research methodologies in the business ethics field.